Therapeutic application of nano-encapsulated pomegranate peel extract attenuated DSS-induced colitis: Antioxidant and anti-inflammatory role and reduction of exaggerated response of endoplasmic reticulum stress - Abdallah Tageldein Mansour; Safaa I. Khater; Hemmat M. Eissa; Helal F. Al-Harthi; Areej A. Eskandrani; Mohammed Ageeli Hakami; Wafa S. Alansari; Amirah Albaqami; Hanan M. Alharbi; Tarek Khamis; Doaa Ibrahim (PLoS ONE, 2025)
The medicinal application of pomegranate peel extract enriched with polyphenols (PPE) as a therapeutic strategy for managing inflammatory bowel diseases (IBD) is still limited. Integrating pomegranate peel extract (PPE) into an effective nanocarrier system could enhance its mechanistic actions, potentially aiding in the remission of colitis. Therefore, this approach aimed to enhance PPE’s stability and bioavailability and investigate mitigating impact of pomegranate peel extract-loaded nanoparticles (PPE-NPs) in a colitis model. Colonic injury was induced by 5% dextran sulfate sodium (DSS) and efficacy of disease progression after oral administration of PPE-NPs for 14 days was assessed by evaluating clinical signs severity, antioxidant and inflammatory markers, expressions of endoplasmic reticulum associated genes and histopathological and immunostaining analysis in colonic tissues. Clinical signs and disease activity index were effectively reduced, and the levels of fecal calprotectin were decreased in groups treated with PPE-NPs compared to DSS group. The colitic group showed a significant increase (P < 0.05) in C-reactive protein (CRP) and myeloperoxidase (MPO) and nitric oxide (NO) (35.60, 163.30 and 280 nmol/g tissue respectively) and higher expression (P < 0.05) IL-17, TNF-α, and IL-1β (increased up to 2.99, 4.36 and 4.90 respectively unlike PPE-NPsIII that recorded reduced levels of CRP, MPO and NO (8,96, 78.30 and 123 nmol/g tissue respectively) and much lower (P < 0.05) levels of IL-17, TNF-α, and IL-1β expression (decreased to 1.23, 1.69 and 1.64, respectively). The most improvement of colon damage PPE-NPsIII group was also associated with the reduction MDA level (P < 0.05) (decreased to 21.60 vs 90.65 in DSS non treated group). The highest glutathione peroxidase, superoxide dismutase and catalase activities were noted in PPE-NPsIII received group (42.60, 50.30 and 62.70 U/mg). Notably, prominent free radical scavenging activities were noticed in group received 150 mg/kg of PPE-NPs as supported by higher scavenging of 1,1-diphenyl-2-picrylhydrazyl (9.85 mg/g) and 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid tested radicals (19.98 mg/g). Balancing between endoplasmic reticulum stressors (ERS), inflammation and autophagy was prominently noted in group treated with 150 mg/kg of PPE-NPs. These findings were supported by subsiding the excessive expression of ERS related genes (CHOP, JUNK, ATF6, BIP, and Elf-2) and immunostaining expression regulation of key markers regulating autophagy (Beclin-2) in this group. The histopathological changes in the colon were less severe in the PPE-NPs received groups (especially at the level of 150 mg/kg) compared to DSS group. Collectively, these findings suggest that the nanoencapsulation of PPE enhances its effectiveness in promoting recovery of colonic tissue damage and achieving remission of colitis.